Keeping up Performance in Times of Crisis : Work Context, Supervisor Support, and Their Relation to Learning Demands and Performance - Kalakoski, Virpi; Lahti, Heidi; Mäkelä, Liisa; Kemppinen, Samu (IMR Press, 2025)
Various job demands and resources influence employee performance. This study examined employees’ perceptions of factors that facilitated or hindered their work performance during a time of crisis—specifically, the COVID-19 pandemic—with a focus on sudden learning demands and supervisor support. A mixed-methods approach was employed, drawing on both quantitative and qualitative data from two studies in the education sector. Study 1 analysed open-ended survey responses using data-driven content analysis (N = 851). The most prevalent themes associated with disrupted workflow and reduced performance included work overload, large group sizes, time pressure, and insufficient resources. A comparison between respondents who appraised learning demands as a hindrance and those who viewed them as a challenge revealed only minor differences. Notably, many identified issues were linked to supervisory practices, prompting a deeper investigation in Study 2. Study 2, a cross-sectional mediation analysis (N = 1242), demonstrated that supervisor support directly and indirectly improved performance by reducing the strain caused by learning demands. Key themes from open-ended responses highlighted the importance of information-sharing, effective communication, and personal contact. The findings suggest that by prioritising clear communication, trust-building, and tangible support, organisations can strengthen supervisor support and, in turn, enhance employee performance during times of crisis.
Keywords: Crisis management; leadership; performance; crisis; COVID-19; learning demands; supervisor support; work performance; fi=Henkilöstöjohtaminen|en=Human Resource Management|